2018
DOI: 10.1177/1074248418784940
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nitrite–Mediated Cardioprotection in Primary Percutaneous Coronary Intervention for ST-Segment Elevation Myocardial Infarction: A Cost-Effectiveness Analysis

Abstract: This first analysis of sodium nitrite as a cardioprotective treatment demonstrates cost-effectiveness. Although more comparative analysis and assessment of longer follow-up times are required, our data indicate the considerable potential of nitrite-mediated cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Animal experiments have confirmed the effectiveness of NO donor, such as organic nitrates and nitrites, in alleviating myocardial ischemiareperfusion injury (14,15). These drugs may reduce infarct area and improve cardiomyocyte survival rate by reducing platelet aggregation, alleviating inflammation, and reducing oxidative stress (16)(17)(18)(19)(20). Although many animal experiments have confirmed that nitrite drugs can protect against myocardial ischemia-reperfusion injury, the clinical trial results of these drugs are not ideal, and their efficacy in patients with acute coronary syndrome (ACS) is still uncertain.…”
Section: Introductionmentioning
confidence: 87%
“…Animal experiments have confirmed the effectiveness of NO donor, such as organic nitrates and nitrites, in alleviating myocardial ischemiareperfusion injury (14,15). These drugs may reduce infarct area and improve cardiomyocyte survival rate by reducing platelet aggregation, alleviating inflammation, and reducing oxidative stress (16)(17)(18)(19)(20). Although many animal experiments have confirmed that nitrite drugs can protect against myocardial ischemia-reperfusion injury, the clinical trial results of these drugs are not ideal, and their efficacy in patients with acute coronary syndrome (ACS) is still uncertain.…”
Section: Introductionmentioning
confidence: 87%